Sentido de Vida en el estudiantado universitario por la virtualización de la educación durante la pandemia provocada por la COVID-19: Modelo de Portafolio de resiliencia - Jiménez-Segura, Flor (Universidad de Costa Rica, 2021)
Without any prior preparation, the student body of the University of Costa Rica, since March 2020, has had to continue their teaching, learning and evaluation process virtually due to COVID-19. The new educational reality of going from a face-to-face education to a virtual one has led it to face different personal situations. The present research aims to analyze the sense of life from the values during the virtualization of education in university students using the Resilience Portfolio Model. The qualitative paradigm, a phenomenological method and the semi-structure interview technique were used. Some results indicated by the students were that they had problems with the family, relationships, connectivity and with teachers who did not have mastery in the virtualization of a course, nor in the management of technological tools, among others. They rescue strengths that let them confront reality in the face of the virtualization of education such as resolving conflicts, making decisions, using technology to maintain relationships with close people and for fun and new personal and professional goals were raised. It can be concluded that the students who participated in the study managed to find sense of life and to be resilient in the midst of the COVID-19 pandemic.